(untitled) (The Journal of Plant Protection Sciences, 2020)
A field experiment was conducted to evalute the efficacy of different plant products against sorghum shoot fly during Kharif 2005 at University of Agricultural Sciences, Dharwad. The different plantproducts used in the study were, Vitex negundo, NSKE, Adathoda vesica, Pongamia glabra, Vincarosea, Butea monosperma, Aloevera @ 5% concentration and were compared with carbofuran 3 G @30 kg. ha-1 to know its efficacy on shoot fly in sorghum ecosystem. The results clearly indicated that NSKE (5%) recorded less eggs of shoot fly (0.40egg/plant), per cent dead heart (14.97%) and maximum grain yield of 13.22 q.ha-1 among different plant products. The next best plant product was found to be V. negundo @ 5% in recording less incidence of shoot fly and obtaining higher grain yield. However,